Design Thinking to Support The Innovative Culture of School Counselors - Suryahadikusumah, Ahmad Rofi; Sari, Kurnia (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2020)
Previous research has found the low ability of millennial school counselors in Palembang to innovate. They only carry out activities that have become a tradition and habit (follower), rarely do program development, even they are used to uploading programs that are shared in group chat. That situation was contradicting with the concept of millennial as innovative generation and the opportunities for self-development provided by technological advances. Design thinking can be referred to as a way of expressing creativity to generate innovative ideas. The research aims to conceptualize the design thinking development of an innovative culture of school counselors. The research was conducted on 30 purposive samples, using descriptive methods which are then combined with the design thinking work step. The research resulted in 1) the main need for the development of an innovative culture through design thinking, 2) a prototype for an innovative culture development activity called "Monday briefing".